An approach to gauge potentials in the non-Abelian ISO(3)-gauge model of defects in solids - Malyshev, C. (Archives of Mechanics, 1996)
A method is proposed to reduce the Cartan structure equations and the Bianchi identities of the non-Abelian ISO(3)-gauge model of defects in solids to the appropriate relations of the theory of disclinations considered as the Abelian ISO(3)-gauge model. As the result, the possibility arises to identify the ISO(3)-gauge potentials in terms of the defect loop densities.